Proinflammatory mucosal-associated invariant CD8+ T cells react to gut flora yeasts and infiltrate multiple sclerosis brain - Gargano, Francesca; Guerrera, Gisella; Piras, Eleonora; Serafini, Barbara; Di Paola, Monica; Rizzetto, Lisa; Buscarinu, Maria Chiara; Annibali, Viviana; Vuotto, Claudia; De Bardi, Marco; D’Orso, Silvia; Ruggieri, Serena; et al. (Frontiers in immunology, 2022)
The composition of the intestinal microbiota plays a critical role in shaping the immune system. Modern lifestyle, the inappropriate use of antibiotics, and exposure to pollution have significantly affected the composition of commensal microorganisms. The intestinal microbiota has been shown to sustain inappropriate autoimmune responses at distant sites in animal models of disease, and may also have a role in immune-mediated central nervous system (CNS) diseases such as multiple sclerosis (MS). We studied the composition of the gut mycobiota in fecal samples from 27 persons with MS (pwMS) and in 18 healthy donors (HD), including 5 pairs of homozygous twins discordant for MS. We found a tendency towards higher fungal abundance and richness in the MS group, and we observed that MS twins showed a higher rate of food-associated strains, such as Saccharomyces cerevisiae . We then found that in pwMS, a distinct population of cells with antibacterial and antifungal activity is expanded during the remitting phase and markedly decreases during clinically and/or radiologically active disease. These cells, named MAIT (mucosal-associated invariant T cells) lymphocytes, were significantly more activated in pwMS compared to HD in response to S. cerevisiae and Candida albicans strains isolated from fecal samples. This activation was also mediated by fungal-induced IL-23 secretion by innate immune cells. Finally, immunofluorescent stainings of MS post-mortem brain tissues from persons with the secondary progressive form of the disease showed that MAIT cells cross the blood–brain barrier (BBB) and produce pro-inflammatory cytokines in the brain. These results were in agreement with the hypothesis that dysbiosis of the gut microbiota might determine the inappropriate response of a subset of pathogenic mucosal T cells and favor the development of systemic inflammatory and autoimmune diseases.